2012
DOI: 10.1016/j.jegh.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Why are inaccurate tuberculosis serological tests widely used in the Indian private healthcare sector? A root-cause analysis

Abstract: Serological tests for tuberculosis are inaccurate and WHO has recommended against their use. Although not used by the Revised National TB Control Programme (RNTCP), serodiagnostics are widely used in the private sector in India. A root-cause analysis was undertaken to determine why serological tests are so popular, and seven root causes were identified that can be grouped into three categories: technical/medical, economic, and regulatory. Technical/medical: RNTCP's current low budget does not allow scale-up of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 20 publications
3
57
0
Order By: Relevance
“…In India, we have shown that although serological TB tests are inaccurate, various players along the value chain profit from their use, and this sustains a market for these tests [34].…”
Section: Why Do We Need To Understand the Diagnostic Ecosystem In Coumentioning
confidence: 96%
“…In India, we have shown that although serological TB tests are inaccurate, various players along the value chain profit from their use, and this sustains a market for these tests [34].…”
Section: Why Do We Need To Understand the Diagnostic Ecosystem In Coumentioning
confidence: 96%
“…This could be due to the preference of these providers to refer patients to local laboratories with whom they have established relations, including financial incentives. 13 About half of the PHCPs were willing to use POC tests for TB if provided free of charge or at a low price (US$ 2.00 per test). This information may be useful for product developers interested in the POC testing market in India.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the paucity of institutional health care payers, the fragmentation of private health-care providers and the lack of national consensus guidelines meant that the companies had to use their own resources to educate the doctors and laboratories about their technologies. Notably, the for-profit nature of the private sector demands that when pricing their products, firms must consider both the affordability for the patient and the provider’s desire to generate profits from the provision of a technology [12,21-23]. This market complexity implies that the commercial success and survival of such companies will depend on their ability to develop ground-breaking strategies in the post-R&D phase also.…”
Section: Discussionmentioning
confidence: 99%